2020
DOI: 10.1039/d0cp05710j
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic tank assisted nicotine sensing property of field effect transistor composed of an atomically thin MoS2channel

Abstract: We investigated the sensor behavior of a field effect transistor, the channel of which is made of atomically thin MoS2 layers, focusing on the interaction of the MoS2 channel with the solution containing target molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…In the case of the second reason, we previously reported that a large difference appeared between the I d – V g curves obtained in air and under UHV condition. 15 Thus, this interface difference may also appear in the V th behavior.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In the case of the second reason, we previously reported that a large difference appeared between the I d – V g curves obtained in air and under UHV condition. 15 Thus, this interface difference may also appear in the V th behavior.…”
Section: Resultsmentioning
confidence: 97%
“…We utilized ultra-high vacuum (UHV) conditions, the details of which are mentioned elsewhere. 15,16 The MoS 2 -FET was installed inside the UHV chamber ($10 À7 Pa) equipped with the required shielded wirings and bonding, in which the MoS 2 channel was cleaned by heating the sample at 150 C, and molecule deposition and FET characterization were done in situ without exposing the device to the air.…”
Section: Methodsmentioning
confidence: 99%
“…Field effect mobility is one of the critical parameters for the characterization of two-dimensional semiconductor materials. The mobility can be estimated using the following equation:where is the transconductance, C ox is the gate capacitance (1.12 × 10 −8 F cm −2 for 285 nm SiO 2 ), 45 L ch and W ch are the MoS 2 channel length and width, respectively, and V d is the drain voltage. In this experiment, a L ch of 7.8 μm, a W ch of 5.9 μm, and a V d of 50 mV were determined.…”
Section: Resultsmentioning
confidence: 99%
“…is the transconductance, C ox is the gate capacitance (1.12 × 10 −8 F cm −2 for 285 nm SiO 2 ), 45 L ch and W ch are the MoS 2 channel length and width, respectively, and V d is the drain voltage. In this experiment, a L ch of 7.8 µm, a W ch of 5.9 µm, and a V d of 50 mV were determined.…”
Section: Resultsmentioning
confidence: 99%